2020
DOI: 10.3390/ijerph17030910
|View full text |Cite
|
Sign up to set email alerts
|

PTP4A3, A Novel Target Gene of HIF-1alpha, Participates in Benzene-Induced Cell Proliferation Inhibition and Apoptosis through PI3K/AKT Pathway

Abstract: Benzene, a commonly used chemical, has been confirmed to specifically affect the hematopoietic system as well as overall human health. PTP4A3 is overexpressed in leukemia cells and is related to cell proliferation. We previously found that HIF-1alpha was involved in benzene toxicity and PTP4A3 may be the target gene of HIF-1alpha via ChIP-seq. The aim of this study is to confirm the relationship between HIF-1alpha and PTP4A3 in benzene toxicity, as well as the function of PTP4A3 on cell toxicity induced by 1,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…[22][23][24] It has been reported in the literature that activation of the PI3K/AKT signaling pathway is involved in benzoquinone-induced cell proliferation and apoptosis, and inhibition of oxidative stress-mediated apoptosis to prevent benzeneinduced haemocytopenia. 25,26 Here we demonstrate a role for the miR-92a-3p/TOB1 axis in the HQ-induced malignant transformation of TK6 cells, providing a reference or basis for studies to intervene in benzene toxicity and prevent treatment.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…[22][23][24] It has been reported in the literature that activation of the PI3K/AKT signaling pathway is involved in benzoquinone-induced cell proliferation and apoptosis, and inhibition of oxidative stress-mediated apoptosis to prevent benzeneinduced haemocytopenia. 25,26 Here we demonstrate a role for the miR-92a-3p/TOB1 axis in the HQ-induced malignant transformation of TK6 cells, providing a reference or basis for studies to intervene in benzene toxicity and prevent treatment.…”
Section: Introductionmentioning
confidence: 67%
“…It has been found that inhibition of the PI3K/AKT pathway can act as a pro‐survival factor in leukemia stem cells and early leukemia in all types of leukemia and it is considered a new therapeutic approach 22–24 . It has been reported in the literature that activation of the PI3K/AKT signaling pathway is involved in benzoquinone‐induced cell proliferation and apoptosis, and inhibition of oxidative stress‐mediated apoptosis to prevent benzene‐induced haemocytopenia 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…PTP4A3 is a dual phosphatase and is known to act on ezrin, cytokeratin and integrin β1 ( 46 48 ). PTP4A3 is involved in the regulation of cell proliferation, migration and invasion through the PI3K-AKT-ERK pathway and destabilizes telomeres through the NFкB-RAP1-TRF2 axis ( 18 , 23 , 24 , 49 ). Moreover, PTP4A3 contributes to the secretion of inflammatory factors, which recruit more immune cells to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non-MDR cancer and normal cells, the levels of ROS and the activity of clearance/antioxidant enzymes are usually increased in drug-resistant cancer cells [ 130 ]. Several studies have indicated that PRL-3 decreases intracellular ROS levels and induces overexpression of glycolysis enzymes and molecules, contributing to enhanced tumor cell proliferation and invasion [ 131 , 132 , 133 ]. Silencing PRL-3 in colon cancer cells has been shown to lead to a ROS-dependent DNA damage response and senescence, indicating a potential link between PRL-3 and acquired resistance [ 121 ].…”
Section: The Relationship Between Prl-3 and Drug Resistancementioning
confidence: 99%